Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/en13236218
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Experimental Study on the Thermophysical Characteristics of DI Water Based Co0.5Zn0.5Fe2O4 Nanofluid for Solar Thermal Harvesting

Abstract: The thermophysical properties of water-based Co0.5Zn0.5Fe2O4 magnetic nanofluid were investigated experimentally. Consequently, the viscosities of 0.25 wt% and 1 wt% Co0.5Zn0.5Fe2O4 nanofluid were 1.03 mPa∙s and 1.13 mPa∙s, each greater than that of the 20 °C base fluid (water), which were increased by 7.3% and 17.7%, respectively. The Co0.5Zn0.5Fe2O4 nanofluid thermal conductivity enhanced from 0.605 and 0.618 to 0.654 and 0.693 W/m·°C at concentrations of 0.25 wt% and 1 wt%, respectively, when the temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The temperature increased with the nanoparticle concentration and light source exposure time. Previous studies by Boldoo et al [38] and Chen et al [39] obtained similar results, and the temperature increased as the nanoparticle concentration increased. For all samples, the temperature rise of the nanofluid was more pronounced than that of the DW at all nanoparticle concentrations.…”
Section: Effects Of Materials Types and Particle Concentrations Of Na...supporting
confidence: 73%
“…The temperature increased with the nanoparticle concentration and light source exposure time. Previous studies by Boldoo et al [38] and Chen et al [39] obtained similar results, and the temperature increased as the nanoparticle concentration increased. For all samples, the temperature rise of the nanofluid was more pronounced than that of the DW at all nanoparticle concentrations.…”
Section: Effects Of Materials Types and Particle Concentrations Of Na...supporting
confidence: 73%
“…When the concentration of the nanofluid is too high, most of the solar radiation is trapped in the top section of the working and cannot travel to the bottom part of the working fluid. In our previous study of PEC with nanofluids, 51 the temperature difference between top and bottom sensors increased with the increasing nanofluid concentrations. The temperature difference between the top and bottom sensors increased from 14.5°C to 18.8°C at a height difference of 30 mm.…”
Section: Introductionmentioning
confidence: 72%
“…Another important application of nanofluids is as working fluids in solar thermal collectors, as in the experimental work by Boldoo et al [3], where they experimentally investigated the thermophysical properties of Co 0.5 Zn 0.5 Fe 2 O 4 and water magnetic nanofluid. With their work, they found that the photothermal energy conversion performance enhanced with the nanofluid concentration and exposure time.…”
Section: Overviewmentioning
confidence: 99%